Attitudes to other ethnicities among New Zealand workers. Issue 3 (3rd August 2015) - Houkamau, Carla; Boxall, Peter
Abstract : Purpose: – The purpose of this paper is to examine the "other-group orientation" (OGO) of New Zealand (NZ) workers as a way of measuring their attitudes to the growing ethnic diversity in the contemporary workplace. Design/methodology/approach: – In all, 500 randomly selected NZ employees were surveyed through computer-assisted telephone interviews. Males, females and ethnic groups were included according to their current proportions in the NZ workforce. Analysis is based on 485 useable cases. Findings: – While New Zealanders generally have a high level of OGO, minority ethnic groups and graduates score higher on OGO. Among people under 38 years, males tend to have a higher OGO, while among those over 38, females tend to be higher. Research limitations/implications: – The study shows the value of studying the attitudes of workers in relation to diversity and OGO. Workers bring their own orientations into the workplace, affecting the way they relate to their co-workers. Social implications: – The pathway to more inclusive workplaces in NZ lies largely in influencing the attitudes and behaviour of NZ Europeans. The study suggests that inclusive educational experiences may be a key part of that process. Originality/value: – While the research shows that NZ workers are generally very positive about ethnic diversity, it reveals variations among ethnic and educational groups in terms of their openness to others.